Early death in active professional athletes: Trends and causes - Lemez, S.; Wattie, N.; Baker, J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The objective of the study was to examine mortality trends and causes of death among professional athletes from the four major sports in North America who died during their playing careers. 205 deceased athletes who were registered as active when they died from the National Basketball Association (NBA), National Football League (NFL), National Hockey League (NHL), and Major League Baseball (MLB) were examined. Results were compared with the Canadian and U.S. general population. The leading causes of death in players reflected the leading causes of death in the Canadian and U.S. general population (i.e., car accidents). Descriptively, NFL and NBA players had a higher likelihood of dying in a car accident (OR 1.75, 95% CI: 0.91-3.36) compared with NHL and MLB players. In addition, NFL and NBA players had a significantly higher likelihood of dying from a cardiac-related illness (OR 4.44, 95% CI: 1.59-12.43). Mortality trends were disproportionate to team size. Overall, death in active athletes is low. Out of 53 400 athletes who have historically played in the four leagues, only 205 died while active (0.38%). Future examinations into the trends and causes of mortality in elite athlete populations will create a better understanding of health-related risks in elite sport